ISOLATION, SCREENING AND MOLECULAR IDENTIFICATION OF NATIVE HYDROCARBON DEGRADING BACTERIA FROM OIL CONTAMINATED SOIL, KRI, IRAQ - Tablo Ahmed; Dilshad Ahmed (Acta Scientifica Malaysia)
There is little information on native hydrocarbon degrading bacterial species, for restoration (bioremediation) of KRI oilfield wastes, Iraq. Thus, an attempt was made to screen, isolate then identify native bacterial isolates, from oil contaminated environments, over five major oilfields. The identification was mainly based on traditional methods and recognized by molecular techniques as confirmatory/comparative analysis. Dynamics of bacterial association was assessed by application of polymerase chain reaction (PCR) method, then reinforcement process of 16S rRNA gene fragment, which occurs right after denaturing gradient gel electrophoresis (DGGE). Out of 55 isolated bacterial strains; three genera (i.e. Bacillus sp., Kocuria sp. and Pseudomonas spp.) were identified as the most potent for hydrocarbon degradation. DNA sequence and phylogenetic analysis confirmed the validity of the species as; Bacillus subtilies-MK000710; Kocuria rosea-MK648258; Pseudomonas fluorescens-LR134300.1 and Pseudomonas putida-GQ303714.1. The four bacterial isolates followed an equal order of occurrence at different geographical locations within the oilfields.